Morphological Interface Between Restorative and Pulp-Capping Materials: A Systematic Review - Desta NT (Dove Medical Press, 2023)
Natnael Teshome Desta Department of Stomatology, Universitat de València, Valencia, SpainCorrespondence: Natnael Teshome Desta, Department of Stomatology, Universitat de València, C/ Gasco Oliag 1, Valencia, 46010, Spain, Email natdes@alumni.uv.esBackground: Bioceramic materials (BCMs) are widely used in vital pulp therapy (VPT) for their biocompatibility and bioactivity; however, their mechanical properties are equally important in the clinical outcome of the pulp-capped teeth.Objective: To carry out an analysis of the research produced on the morphology of the interface between BM and restorative materials (RM) through a systematic review.Methodology: An electronic search was performed in Scopus, PubMed, and Web of Science until December 9, 2022. The keywords used in combination with truncation and Boolean operators were: (morphology OR filtration OR porosity) AND (silicate OR composite) AND (cement) AND ("pulp capping" OR "vital pulp therapy" OR "vital pulp treatment").Results: Of the 387 articles initially retrieved from the electronic search databases, 5 articles met the criteria for qualitative data collection. MTA and Biodentine were the most studied BCMs. All the articles used a scanning electron microscope as a method of evaluating the samples. Sample sizes and setting times of RM and BCMs differed between studies. Three out of 5 studies used similar conditions of recorded temperature and humidity of 37°C and 100%, respectively.Conclusion: The different biomaterials used, the application of adhesive systems, humidity and restoration time affect the bonding performance and the ultrastructural interface between BCMs and RMs. The scarcity of research on this point makes it necessary to delve into it and study new materials to obtain more scientific evidence.Keywords: silicate, cement, vital pulp therapy, morphology, interface